An Addition of U0126 Protecting Heart Grafts From Prolonged Cold Ischemia-Reperfusion Injury in Heart Transplantation: A New Preservation Strategy. Issue 2 (February 2021) - Zheng, Hao; Su, Yale; Zhu, Cuilin; Quan, Douglas; Skaro, Anton I.; McAlister, Vivian; Lacefield, James C.; Jiang, Jifu; Xue, Peng; Wang, Yefu; Zheng, Xiufen
Abstract : Background: Ischemia-reperfusion injury (IRI) is the major cause of primary graft dysfunction in organ transplantation. The mitogen-activated protein kinase/extracellular signal-regulated kinase (ERK) signaling pathway plays a crucial role in cell physiological and pathological processes including IRI. This study aims to investigate whether inhibition of ERK signaling with U0126 can prevent prolonged cold IRI in heart transplantation. Methods: Rat cardiac cell line H9c2 cells were treated with U0126 before exposure to hypothermic hypoxia/reoxygenation (H/R) conditions. The effect of U0126 on H9c2 cells in response to H/R stress was determined by measuring cell death, reactive oxygen species production, mitochondrial membrane potential, and ERK signaling activation. Mouse syngeneic heterotopic heart transplantation was conducted, where a donor heart was preserved in the University of Wisconsin (UW) solution supplemented with U0126 for 24 hours at 4°C before transplantation. Heart graft function, histopathologic changes, apoptosis, and fibrosis were measured to assess IRI. Results: Phosphorylated ERK was increased in both in vitro H/R-injured H9c2 cells and in vivo heart grafts with IRI. Pretreatment with U0126 inhibited ERK phosphorylation and prevented H9c2 cells from cell death, reactive oxygen species generation, and mitochondrial membrane potential loss in response to H/R. Preservation of donor hearts with U0126-supplemented solution improved graft function and reduced IRI by reductions in cell apoptosis/death, neutrophil infiltration, and fibrosis of the graft. Conclusions: Addition of U0126 to UW solution reduces ERK signal activation and attenuates prolonged cold IRI in a heart transplantation model. ERK inhibition with U0126 may be a useful strategy to minimize IRI in organ transplantation.